Does skill-biased technical change diffuse internationally? - Patrick Schulte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper studies the question whether skill-biased technical change diffuses internationally and that way contributes to the increasing relative skill demand in other countries. So far, the role of skill-biased technology diffusion has hardly been studied empirically. Using new sectoral data for a panel of 40 emerging and developed countries, 30 industries (covering manufacturing and service industries) and 13 years (1995-2007), the analysis shows that skill-biased technology diffusion is statistically and economically important in explaining skill-biased technical change. Countries further away from the skill-specific technological frontier subsequently show higher skill-specific productivity growth. For that, the bilateral distance between two countries proves to be an important mediating factor, whereas intersectoral trade linkages, so far, explain only a small part of it. The main results hold for both, developed and emerging countries.
urn:nbn:de:bsz:180-madoc-405187
Keywords: F16; J24; O14; O33; C67; 330; skill-biased technical change; technology diffusion; distance; inputoutput linkages; industry-level data; emerging and developed countries